Dialectic and gospel in the development of Hegel's thinking - Crites, Stephen (University Park, Pennsylvania The Pennsylvania State University Press, 1998)
Hegel came to maturity as a philosopher during the first years of the nineteenth century, developing through prodigious intellectual struggles a highly original conception of dialectic as a method for rationally comprehending traumatic historical change. At the same time, he continued a process begun earlier, of critical engagement with the Christian gospel and its historical ethos. Dialectic and Gospel in the Development of Hegel's Thinking tells the story of this interplay as it develops in Hegel's thinking. It culminates in a freshinterpretation of the Phenomenology of Spirit and a detailed commentary on larger portions of the text relevant to that story.
Includes bibliographical references (pages 561-563) and index
Keywords: Theology, Doctrina -- Germany -- History -- 19th century; Philosophy and religion -- History -- 19th century; Dialectic -- History -- 19th century